A stereo EEG study in a patient with sleep-related hypermotor epilepsy due to DEPDC5 mutation. (December 2017) - Ferri, Lorenzo; Bisulli, Francesca; Mai, Roberto; Licchetta, Laura; Leta, Chiara; Nobili, Lino; Mostacci, Barbara; Pippucci, Tommaso; Tinuper, Paolo
Abstract: Purpose: Dishevelled EGL-10 and pleckstrin domain-containing protein 5 (DEPDC5) mutations are found in a wide spectrum of focal epilepsies ranging from epilepsy caused by malformation of cortical development to non-lesional epilepsy, including sleep-related hypermotor epilepsy (SHE). A surgical approach has been anecdotally reported in patients with DEPDC5 mutations, but most of these cases had a lesional etiology. Methods: We describe a stereo-EEG (SEEG) study in a patient with drug-resistant/non-lesional SHE. Patient was screened for known mutations associated with SHE. Results: SEEG disclosed bilateral synchronous and independent activity prevailing on the right central-anterior cingulate cortex, without a clear spatially defined epileptogenic zone. Due to the lack of a clear epileptogenic zone, surgery was contraindicated. Years later a DEPDC5 mutation was identified. Conclusion: We suggest that genetic analysis should be considered before performing SEEG study in a patient with drug resistant non-lesional SHE, in the presence of seizures in wakefulness and unclear anatomo-electroclinical correlation. If DEPDC5 mutations are identified, the presurgical evaluation should be tailored to look for MRI-negative focal cortical dysplasia and a wide epileptogenic network. The appropriate management and potential benefit of surgery for genetic non-lesional epilepsy have yet to be clarified.